2012
DOI: 10.7888/juoeh.34.175
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Transpelvic Prosthetic Socket for a Patient with Spinal Cord Injury Sustaining Right Partial Hemipelvectomy and Left Hip Disarticulation

Abstract: : A bucket-type transpelvic socket was fabricated for a man with paraplegia from spinal cord injury, who underwent right partial pelvic amputation and left hip disarticulation. His main problem was inability to sit due to asymmetrical pelvic shape. We prescribed a transpelvic prosthetic socket to enable him to sit again. The socket consisted of a dual structure: a hard frame and soft liner. The main features of the socket were redistribution of pressure to prevent recurrence of pressure ulcer, and a slightly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Although the stair ascend and descend score had a reverse relationship with amputation level, it was not statistically significant. In a study on war-related hip amputations, the stair domain had the lowest score, 17 and Roehrig et al 24 reported similar low results as well. In another study, Ashraf et al 20 evaluated 335 bilateral lower limb amputees using the Barthel index.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Although the stair ascend and descend score had a reverse relationship with amputation level, it was not statistically significant. In a study on war-related hip amputations, the stair domain had the lowest score, 17 and Roehrig et al 24 reported similar low results as well. In another study, Ashraf et al 20 evaluated 335 bilateral lower limb amputees using the Barthel index.…”
Section: Discussionmentioning
confidence: 90%
“…Other studies done on Iraq–Iran war amputees reported the same age group (range: 18–25 years). 1114,1719…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations